2002
DOI: 10.1093/ndt/17.11.2003
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective analysis for aetiology and clinical findings of 287 secondary amyloidosis cases in Turkey

Abstract: FMF is the leading cause of secondary amyloidosis in Turkey, followed by tuberculosis. Oedema accompanied by proteinuria is the most prominent presenting finding, and hypotension seems to be common among these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
59
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(68 citation statements)
references
References 15 publications
4
59
0
3
Order By: Relevance
“…The overall incidence of systemic secondary amyloidosis in Western nations ranges from 0.5 to 0.86%, but increases significantly in certain patients (2)(3)(4). Deposition of the amyloid fibril in secondary amyloidosis (AA amyloid) can lead to progressive loss of splenic and renal functions.…”
mentioning
confidence: 99%
“…The overall incidence of systemic secondary amyloidosis in Western nations ranges from 0.5 to 0.86%, but increases significantly in certain patients (2)(3)(4). Deposition of the amyloid fibril in secondary amyloidosis (AA amyloid) can lead to progressive loss of splenic and renal functions.…”
mentioning
confidence: 99%
“…Renal amyloidosis is the most frequent type of systemic amyloidosis with a prevalence between 0.5% and 0.86% in various autopsy series 19. Secondary amyloidosis is associated with a variety of chronic inflammatory diseases such as osteomyelitis, inflammatory bowel diseases, FMF, tuberculosis, bronchiectasis, and rheumatoid arthritis 20, 21.…”
Section: Discussionmentioning
confidence: 99%
“…The time lapse between the onset of inflammatory bowel disease and an amyloidosis diagnosis is variable: amyloidosis is usually diagnosed 10–15 years after inflammatory bowel disease diagnosis, is sometimes discovered simultaneously with inflammatory bowel disease, and is rarely described before inflammatory bowel disease onset 22. (ii) Chronic osteomyelitis, where amyloidosis due to osteomyelitis is a late and infrequent complication 20, 23; in a large series on secondary amyloidosis, osteomyelitis was the etiologic condition in 2% of cases 20. (iii) CIPA and NTRK1 signaling pathway, where patients with CIPA show several immune and inflammatory abnormalities 14, 15.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10] Also in Turkey, two retrospective analysis of secondary amyloidosis cases revealed that FMF is the most frequent cause of secondary amyloidosis, with a rate of 64% and 30.5%. [11][12][13] Colchicine controls the frequency of the attacks and progression of amyloidosis. However, 5-10% of the patients do not respond to therapy.…”
Section: Discussionmentioning
confidence: 99%